The Student Club as a Tool for Attracting Youth Audience to Museums - Valery E. Gordin; Irina A. Sizova; Elizaveta K. Dementyeva; Anna N. Kudelkina; Marcellinus Dike (Peoples' Friendship University of Russia (RUDN University), 2022)
The authors describe the possibility of using a differentiated approach based on vocational education in the field of art and culture as a new criterion for attracting youth audiences to museums in the digital era. A distinctive feature of the differentiated approach in the activities of museum student clubs is the targeted impact on various groups of young people, taking into account their age and level of art training in the development of museum programs. In order to assess the applicability of the differentiated approach to working with young people in museums, the members of student clubs of the two largest museums in Russia, i.e., the Hermitage and the Russian Museum, were surveyed. Expert interviews with the staff of the student clubs were also conducted. Based on the results of the analysis, the authors identified three groups of the young people, which were designated as "interested," "advanced" and "proficient." The criteria for dividing into the groups were differences in the educational level of the students in the field of art and culture. This division allowed to determine the forms of the most attractive museum events for the identified groups of students. The results of the study may be useful in working with the youth audience in other museums.